2013
DOI: 10.5665/sleep.3224
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Findings Related With Mild Cognitive Impairment in Idiopathic Rapid Eye Movement Sleep Behavior Disorder

Abstract: Electroencephalographic slowing, especially during rapid eye movement sleep and olfactory dysfunction, was revealed to be associated with cognitive decline in idiopathic rapid eye movement sleep behavior disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 39 publications
4
21
2
Order By: Relevance
“…That study was the first to show impaired cortical activation during both wakefulness and REM sleep in iRBD although changes in sleep architecture were absent. The results were replicated by studies conducted in later years [25,35]. …”
Section: Quantitative and Qualitative Eeg Findings In Irbdsupporting
confidence: 77%
See 4 more Smart Citations
“…That study was the first to show impaired cortical activation during both wakefulness and REM sleep in iRBD although changes in sleep architecture were absent. The results were replicated by studies conducted in later years [25,35]. …”
Section: Quantitative and Qualitative Eeg Findings In Irbdsupporting
confidence: 77%
“…These findings strongly affected the relationship between cognitive decline and EEG slowing in patients with iRBD. In line with this report, our study also revealed that MCI determined using the Montreal cognitive assessment scale [47] was observed in more than 75% of the iRBD patients, and that age and log(θ power during REM sleep) was significantly associated with the this score in multiple regression analysis in this patients population [35]. In addition, a decrease in the score of the Sniffin' Stick test (threshold-discrimination-identification score), which is known as an early LBD marker [48], was significantly associated with the Montreal cognitive assessment score in this analysis.…”
Section: Relationship Between Eeg Slowing and Cognitive Impairment Insupporting
confidence: 73%
See 3 more Smart Citations